Trace Elements in Children With Pre-Dialysis and End-Stage Renal Disease - Abd Alsalam, Asmaa; H Ali, Ruaa; K Hussain, Haider; Mahdi, Montadher Ali (Scripta Medica, 2024)
Background/Aim: Chronic kidney disease (CKD) impacts 11-13 % of world wild population and can lead to end-stage renal disease (ESRD). Paediatric CKD is connected with considerable morbidity and necessity for early management. Trace elements as iron (Fe), zinc (Zn) and copper (Cu) are required for a variety of physiological activities and may influence CKD progression. The main goal of this work was to analyse the amounts of trace elements among children with CKD and ESRD and their potential as disease stage biomarkers.Methods: The study comprised 40 pre-dialysis CKD patients, 40 dialysis-dependent ESRD patients and 40 healthy controls aged 0 to 19 years. Blood samples were obtained and tested for Fe, Zn and Cu levels utilising flame-atomic absorption spectrophotometry (FAAS). Anthropometric data, such as age, body mass index (BMI) and blood pressure, were also collected. The statistical calculations were done by the utilising of SPSS version 25.0. Results: Trace element levels varied significantly between groups. Cu levels were higher, while Fe and Zn concentrations were lower in CKD and patients on dialysis compared to controls, with Zn exhibiting the greatest drop. Zn had the highest accuracy as a biomarker for CKD and ESRD, with an AUC of 0.999, sensitivity of 100 % and specificity of 98 %.Conclusion: Zn is a promising biomarker for detecting CKD development and distinguishing between CKD stages and ESRD. Regular trace element monitoring is critical for controlling paediatric chronic kidney disease and improving patients’ consequences. Further research is needed to determine the therapeutic potential of trace element management in CKD.